Technologizing Touch: Tactile Magic, Education, and Domestication in Apple iPad Advertisements - Archer, Jason Edward (AoIR Selected Papers of Internet Research, 2013)
Touch may be the most intimate but least understood forms of communication. Its primacy made it a third sense behind seeing and hearing. However, as touchscreen technologies permeate the cultural landscape, and tactility enters scholarly discussions, the importance of understanding the relationships between tactility and human-machine communication in everyday life is increasingly felt. This study provides a discourse analysis about the tactility of human-machine communication by using Apple iPad advertisements as case studies. The investigation uncovers three dominant discourses that position the iPad as providing a magical tactile experience through intuitive, everyday activities, confined within the critical space of domesticity.